TOPICS : GAUSS 'S THEOREM. INTEGRAL EXPRESSION OF THE HYPERGEOMETRIC FUNCTION ACCORDING TO THE DALANBER PRINCIPLE - B. B. Makhmudov, F. F. Vokhobov (Galaxy International Interdisciplinary Research Journal, 2022)
The article considers boundary value problems for hypergeometric functions and their differential equations, problems in the integral form of hypergeometric functions. The hypergeometric function of Gauss, the Dalanber principle was used .